Effects of current density on the formation and microstructure of Sn–9Zn, Sn–8Zn–3Bi and Sn–3Ag–0.5Cu solder joints - Othman, R.; Binh, D.N.; Ismail, A.B.; Long, B.D.; Ariga, T. (Elsevier, 2012)
The formation and growth of intermetallic compounds (IMCs) between lead-free solder alloys and Cu substrate were investigated. Cu6Sn5 IMC was formed in the Sn–3Ag–0.5Cu solder joint, whilst Cu5Zn8 IMC was formed in the Sn–9Zn and Sn–8Zn–3Bi solder joints after soldering. After exposure to a current density of 500 A/cm2 and 100 °C for 120 h, a sub-layer was detected in the Sn–3Ag–0.5Cu solder joint and this was identified as IMC Cu3Sn. The growth of the IMCs increased with increasing current density and was found to be faster at the anode side. Under the same testing conditions, the results showed that the growth rate or the thickness of the IMCs was highest in Sn–9Zn, followed by Sn–8Zn–3Bi, and the least being in Sn–3Ag–0.5Cu. The microstructure of Sn–3Ag–0.5Cu solder joint was observed to exhibit changes under exposure to current, whilst the microstructure of the Sn–9Zn and Sn–8Zn–3Bi solder joints remain unchanged, except for the increase in IMCs thickness.